Which Spanish Living Kidney Donors Fear Post Donation Kidney Failure?. (July 2018) - Avinyo, Nuria; Torres, Xavier; Menjivar, Ana; Delgado, Isabel; Rangil, Teresa; Cañas, Laura; Lorenzo, Dolores; Fernandez, Anton; Martinez, Montserrat; Valles, Carmen; Vila, Anna; Arcos, Emma; et al.
Abstract : PI15/00550 - Characterization of the fear of kidney failure in the living kidney donor. Background: The impact of fearing the failure of the non-donated kidney is unknown in Spanish donors. For this reason, we aimed at assessing the validity of the Spanish version of the Fear of Kidney Failure Questionnaire (FKF), along with characterizing living donors with higher fear of kidney failure. Methods: 205 living kidney donors (LKDs) were randomly selected and stratified by year of donation (2005-2015). 139 general population participants without history of, or a current renal disease and/or without first-degree relatives suffering a renal disease were recruited as comparison group. Reliability of the FKF was assessed. The FKF criterion validity was evaluated by calculating its linear relationship with anxiety, depression, and fear-related personality dimensions. Divergent validity was verified by assessing whether the FKF was unrelated to personality dimensions non-relevant for fear states. LKDs were grouped by Cluster Analysis of the FKF scores. Clusters were compared on demographic and clinical variables to describe those LKDs with higher scores in the FKF, which were further characterized by calculating the most specific logistic regression model. Results: The internal consistency of the FKF was acceptable for the whole sample (α=0.95), and the LKDs (α=0.91) and general population (α=0.94) subsamples. Temporal stability of the FKF was acceptable (ICC=0.93). Factor analysis showed that the FKF was composed by a single factor explaining 83.5% of variance. Both for the whole sample and the LKDs and general population subsamples, the FKF was positively correlated with depressive and anxiety symptoms, and neuroticism (convergent validity). The FKF was unrelated to extroversion, openness to experience and conscientiousness (divergent validity). Fear of Kidney Failure in the general population subsample almost doubled the mean of the LKDs subsample. The FKF Cluster Analysis classified LKDs in three groups: absence of fear (68%), moderate fear (20%), and high fear of kidney failure (12%). Groups did not differ in demographics or donation outcomes. No differences were observed between groups in regret for having donated. However, higher FKF scorers were somewhat less satisfied with the experience of donation. This subgroup also showed a higher percentage of potential cases of depressive (16%) and anxiety disorders (20%), a worse quality of life, and higher scores in neuroticism. A higher percentage of these donors (20%) were followed both by the Nephrologist and the Family Doctor. Multivariate logistic regression showed that, once controlled the effect of presenting a potential depressive or anxiety disorder, FKF higher scorers were best characterized by higher scores in neuroticism. Conclusions: Post donation fear of kidney failure is infrequent in Spanish LKDs. However, a subgroup of them, best characterized by a higher neuroticism, shows elevated FKF scores, a worse quality of life, and might present with anxiety and depressive disorders. This work has been funded by the project PI15/00550, integrated in the Plan Nacional I+D+I and co-funded by ISCIII-Subdirección General de Evaluación and European Regional Development Fund (ERDF).